Interactive E-Learning Courses as a New Teaching Method: Kursus E-Learning Interaktif sebagai Metode Pengajaran Baru - Usmonov Murod Sodiqovich; Abdullayev Xolxuja Burxonovich; Suvonqulov Baxtiyor Mamarasulovich (Universitas Muhammadiyah Sidoarjo, 2020)
This article discusses the use of interactive training courses, their features, differences from ordinary training courses. The article also develops a model of a multimedia interactive e-learning course and discusses its advantages.